Linear Algebra Based Controllers Design and Applications - Scaglia, Gustavo; Serrano, Mario Emanuel; Albertos, Pedro (Springer International Publishing : Imprint: Springer, 2020)
XV, 147 p. 67 illus., 41 illus. in color.